ANTESEDEN EMPLOYEE TURNOVER - Heryadi Fardilah (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2017)
This research is concerning the effect of workplace environment, job satisfaction, and job performance on employee turnover, and the background is to get the convenience of employees condition, the satisfaction of job results, maximum performance, and keep and reduce in and out employees. The purpose of this research is to see how far the influence of workplace environment, job satisfaction, and job performance on employee turnover. Planning of this research uses primary data that is got by handing over questioners to 200 employees in Telecommunication company in East Jakarta. The analysis method which is used is double regresi. Results of this research give conclusion that there's a positive and significant influence of workplace environment, job satisfaction, and job performance on employee turnover.